2011
DOI: 10.3178/hrl.5.83
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in evapotranspiration over East Asian forest sites. I. Evapotranspiration and decoupling coefficient

Abstract: Abstract:Evapotranspiration (ET) is not only a vital component of water budget, but also plays an important role in the energy budget of the earth-atmospheric system, ultimately driving many regional and global scale climatological processes. This paper describes the ET characteristics and factors controlling ET across the 17 forest sites in East Asia (2°S to 64°N latitude). ET was measured using the eddy covariance technique at each site. Daytime dry-canopy data for the growing season were used in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…This is also supported by the relatively low Ω values in each site, indicating that the sites are more coupled with their microclimate, rather than each of them being controlled by local more large-scale differences [18]. However, in a study developed by Khatun et al [34], Ω values similar to the ones we have obtained here were observed. The different Ω values were explained by differences in environmental and vegetation structural attributes, rather than actual differences in vegetation type.…”
Section: Water Fluctuation Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…This is also supported by the relatively low Ω values in each site, indicating that the sites are more coupled with their microclimate, rather than each of them being controlled by local more large-scale differences [18]. However, in a study developed by Khatun et al [34], Ω values similar to the ones we have obtained here were observed. The different Ω values were explained by differences in environmental and vegetation structural attributes, rather than actual differences in vegetation type.…”
Section: Water Fluctuation Effectssupporting
confidence: 88%
“…Jarvis and McNaughton [18] also observed this increasing coupling as a result of water stress since canopies with more coupling are going to be more controlled by stomatal conductance and thus water fluctuations. Khatun et al [34] have also found this increased coupling as a result of water stress, and therefore we believe a less coupled canopy may be more resilient during periods of water stress. Growing season differences may also help to explain the discrepancies observed in the natural grassland and perennial crop sites compared to the annual cropland site.…”
Section: Water Fluctuation Effectssupporting
confidence: 62%
“…ET represents latent heat flux, and is a key component of water and energy balance. EC flux observations have been widely used to examine ecosystem carbon fluxes (Baldocchi, 2008;Amiro et al, 2010;Schwalm et al, 2010), ET (Ryu et al, 2008;Khatun et al, 2011), and water use efficiency (WUE) (Ponton et al, 2006;Yu et al, 2008a) worldwide. Flux observations have also been upscaled to assess terrestrial carbon and water dynamics at regional, continental, and global scales (Xiao et al, 2008(Xiao et al, , 2012Sun et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Single studies that have employed a consistent method to estimate across multiple species are rare (e.g. Stoy et al, 2006;Khatun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%